Kampanye Gunakan Hak Suara dan Jangan Golput Pada Pemilu 2024 untuk Generasi Muda - Muhammad Ridha Iswardhana; Maf'ulillahi Zakinah; Gita Ardya Maharani; Widia Grace Tayan; Adinia Nuraini (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2023)
The young generation is a future leader and the most significant number of voters in the 2024 General Election. In this election, Indonesia will elect the President and his deputy, Members of the People's Representative Council at the national level, Members of the Regional Representative Council, and Members of the Regional Representative Council at the provincial and city levels, Governors and Regents or Mayors at the regional level. General elections will be held on February 14, 2024, and November 27, 2024. However, many people still need to understand the importance of this five-yearly national activity. Many young people are apathetic and do not care about the 2024 elections. This activity aims to provide education and invite young people to participate in the upcoming elections as voters. This service was conducted on 05-06 May 2023 at the Yogyakarta Sultanate Palace's Kidul Square and Mandala Krida Stadium. Based on the implementation of this service, it was found that the millennial generation was interested in participating in the 2024 elections but needed to understand the selected candidates. In addition, most of the audience has been registered as a Final Voter List (DPT). This reality shows that millennials can vote. However, most young people have already chosen the presidential candidate and party. At the same time, there are still many representatives at the national and regional levels who have yet to make their choice.